Akselerasi Pelatihan Pengembangan Produk Unggulan - Aprila, Bord Nandre; Rahman, Sarli; Fransisca, Luciana; Irman, Mimelientesa; Fitriyani, Fitriyani; Syahputra, Hidayat; Pujiono, Pujiono; Setyawan, Onny (Institut Bisnis dan Teknologi Pelita Indonesia, 2024)
Superior product development is a strategic step in creating competitive products and meeting consumer needs effectively. The training held in Pekanbaru aims to increase the capacity of business actors in producing innovative and high-quality products, as well as build a network of collaboration with academics and industry. The focus of the training is directed at accelerating the product development process through various topics, including business feasibility analysis, marketing strategies, consumer behavior, and market segmentation techniques. With an approach that involves presentations, simulations, and interactive discussions, participants gain an in-depth understanding and practical skills to apply the training materials. The evaluation conducted through feedback aims to assess the effectiveness of the training and identify the need for further training. The results of this activity show an increase in participants' understanding and strengthen collaboration between business actors, academics, and the government in supporting the development of competitive superior products in the market.